Enemies of the cross suffering, truth, and mysticism in the early Reformation - Evener, Vincent (Oxford University Press USA - OSO, 2020)
Enemies of the Cross examines how suffering and truth were aligned in the divisive debates of the early Reformation. Vincent Evener draws on seldom-used sources and describes how Protestants and radicals brought medieval mystical teachings into new frameworks that rejected spiritual hierarchy.